The relative value and role of copper within an Egyptian New Kingdom economic context: Using production, trade and use of copper as indicators of copper's value - Johnsen, Daniel (AUC Knowledge Fountain, 2018)
Ancient Egypt's use of copper was extensive and represented a sizable portion of Egypt's metallurgical focus. There has been limited discussion about the metallurgical technologies of the New Kingdom or the role of copper in an economic context. This thesis examines the modes, methods and technologies involved in copper acquisition, processing and use to ascertain and demonstrate the relative value of copper within the economy of New Kingdom Egypt. It is argued that copper represented one of the greatest and most widely used commodities available to the Egyptians. Various economic theories are also highlighted to compare possible effects of copper on both local and foreign trade. This work is designed to elicit further study into the interplay between metallurgy and economic development and provide a possible methodology for such a study.